Quadricuspid Pulmonic Valve, Pulmonary Artery Aneurysm, and Apical Hypertrophic Cardiomyopathy: A Rare Combination. (June 2018) - Guijarro-Contreras, Ana; Pardo-Martínez, Patricia; Cham, Matthew; Macaluso, Frank; Sanz-Salvo, Javier
Abstract : Supplemental Digital Content is available in the text.